-7(-3u+5)-7u=6(u-4)-9

Simple and best practice solution for -7(-3u+5)-7u=6(u-4)-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(-3u+5)-7u=6(u-4)-9 equation:



-7(-3u+5)-7u=6(u-4)-9
We move all terms to the left:
-7(-3u+5)-7u-(6(u-4)-9)=0
We add all the numbers together, and all the variables
-7u-7(-3u+5)-(6(u-4)-9)=0
We multiply parentheses
-7u+21u-(6(u-4)-9)-35=0
We calculate terms in parentheses: -(6(u-4)-9), so:
6(u-4)-9
We multiply parentheses
6u-24-9
We add all the numbers together, and all the variables
6u-33
Back to the equation:
-(6u-33)
We add all the numbers together, and all the variables
14u-(6u-33)-35=0
We get rid of parentheses
14u-6u+33-35=0
We add all the numbers together, and all the variables
8u-2=0
We move all terms containing u to the left, all other terms to the right
8u=2
u=2/8
u=1/4

See similar equations:

| 9x=840 | | 5y-12=y-5 | | -4(v-9)=-7v+18 | | 3x-2=8x+18 | | 21x=-210 | | 5x2=62 | | -3(-5+7)+-5x-5+4=23 | | -3(-1+7)+-5k+4=23 | | 2.25x8=18.00 | | -199=-7(-3x+2) | | 126=7(4a+6) | | 3(3x+2)=2(6x-3) | | −y2+4y=−32 | | 6/c-1/c= | | 140=-7(n-7)-6n | | -142=3-5(8b-3) | | 3y+12y=23 | | r+3+3=4 | | 3y+13y=23 | | 3x-6+3x=12 | | -6x-3=7x-9 | | 2(c-12)=10 | | 50+60x=50x+80 | | -4x+1=3 | | (g−9)/1 = –1 | | 7(-5+3m)+6=97 | | 3+3(-5x+8)=-93 | | ―4x+1=3 | | 2x-5-6=-6 | | 5-4d=3d+5 | | 8-g=g+3 | | 6s+6s+2s+s+s=102 |

Equations solver categories